Warfarin-ciprofloxacin interaction complicated by subcapsular renal hematoma and retroperitoneal hematoma: Case report - Masoud Basheer Alshammari; Zainab Ali Alhassar; Abdulla Abduljaleel Alkhalifa; Abdulmalik Abdulaziz Alkhamis; Hatem Hamed Al-Thubiany (Urology Case Reports)
Spontaneous, non-traumatic bleeding into the subcapsular and perirenal space is a rare and potentially fatal condition known as Wunderlich syndrome (WS). It has a variety of causes including the usage of anticoagulation. Many anticoagulants including warfarin can interact with other medication and lead to potentially fatal complications, Herein, we report a case of a 47 year old female on warfarin who developed subcapsular renal hematoma and retroperitoneal hematoma after the completion of ciprofloxacin treatment course.